Mitochondria dysfunction of Alzheimer's disease cybrids enhances Aβ toxicity - Cardoso, Sandra M. (2004)
Alzheimer's disease (AD) brain reveals high rates of oxygen consumption and oxidative stress, altered antioxidant defences, increased oxidized polyunsaturated fatty acids, and elevated transition metal ions. Mitochondrial dysfunction in AD is perhaps relevant to these observations, as such may contribute to neurodegenerative cell death through the formation of reactive oxygen species (ROS) and the release of molecules that initiate programmed cell death pathways. In this study, we analyzed the effects of beta-amyloid peptide (A03B2) on human teratocarcinoma (NT2) cells expressing endogenous mitochondrial DNA (mtDNA), mtDNA from AD subjects (AD cybrids), and mtDNA from age-matched control subjects (control cybrids). In addition to finding reduced cytochrome oxidase activity, elevated ROS, and reduced ATP levels in the AD cybrids, when these cell lines were exposed to A03B2 1201340 we observed excessive mitochondrial membrane potential depolarization, increased cytoplasmic cytochrome c, and elevated caspase-3 activity. When exposed to A03B2, events associated with programmed cell death are activated in AD NT2 cybrids to a greater extent than they are in control cybrids or the native NT2 cell line, suggesting a role for mtDNA-derived mitochondrial dysfunction in AD degeneration.